E-Pengajian Am Mengenal Pasti Graf In Mobile Learning Application - Abu Hanifah, Haziyah; Mustafa, Mastika (Journal of Computing Technologies and Creative Content, 2021)
Pengajian Am is one of the subjects required to pass any semester of the Sijil Tinggi Persekolahan Malaysian exam. Alih Bentuk Komunikasi (Linear Kepada Bukan Linear) is one of the topics in the field. The goal of this project is to examine mobile learning applications in e-Pengajian Am (Mengenal Pasti Graf). The title of this application is E-Pengajian Am (Mengenal Pasti Graf). STPM students are the target users of this initiative. The purpose of this application is to create a mobile learning application for the Pengajian Am graph subject in Semester 2 in an effective way. In addition, this application is planned for STPM students to use sufficient resources for simple learning. This is really important so students are expected to read and practise any of the subjects taught during the semester. E-Pengajian A smartphone learning framework uses the ADDIE model. This model was selected because it has organized elements that are ordered step by step. Analysis, design, development, implementation and evaluation are essential steps of the ADDIE model in order to make mobile learning effective. Overall, this project is very good at helping STPM students learn because the content is easy to understand. The findings of the analysis which have been obtained indicate that they are pleased with it and have made this a useful application.